2018
DOI: 10.14311/gi.17.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Malaria Prevalence Rate in Lagos State Using Multivariate Environmental Variations

Abstract: The aim of this research is to establish the significant effect of environmental factors on malaria prevalence rate within the Local Government Areas of Lagos State. The methodology used was to carry out a statistical analysis of these various environmental factors with the malaria prevalence cases that was recorded in Lagos State using a 5 years data from 2009-2013 of malaria prevalence cases recorded with environmental data for the same time frame, and to further use GIS to show the various Local Government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The outcomes showed distinct patterns of malaria morbidity across the different states in the Southwest zone. These findings corroborate prior investigations studying the relationship between meteorological factors and malaria morbidity countrywide (8,17,18,23). Importantly, however, this study is the first in the region showing the connection between malaria cases and weather variations across the Southwest states at both spatial and temporal dimensions using data from a single source (DHIS2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The outcomes showed distinct patterns of malaria morbidity across the different states in the Southwest zone. These findings corroborate prior investigations studying the relationship between meteorological factors and malaria morbidity countrywide (8,17,18,23). Importantly, however, this study is the first in the region showing the connection between malaria cases and weather variations across the Southwest states at both spatial and temporal dimensions using data from a single source (DHIS2).…”
Section: Discussionsupporting
confidence: 91%
“…by Omogunloye et al(17) also show that maximum temperatures were statistically significant with malaria prevalence in different local government areas in Lagos State, which correlate with findings in this study. Likewise, the findings for the current study have been shown to be similar to those conducted in Jos and Kano states (23), where it was found that the association between malaria incidence and local weather varies at different lag times and direction.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…There were over 60,000 cases of malaria in Ikeja in 2013. 18 The closeness of the city to Lagos Lagoon and the poor drainage system found in some of its areas could provide suitable breeding sites for mosquito malaria parasite vectors, enabling stable transmission of malaria. As far as HIV/AIDS is concerned, its transmission is largely associated with large population sizes and fluid movement of people in and out of the state.…”
Section: Methodsmentioning
confidence: 99%